Discussion on the Non-Linear Stability of Short Hydrodynamic Bearings by Applying Rabinowitsch Fluid Model - Huaiqing Lu; Chunyan Cheng; Zhuxin Tian (Lubricants)
Using the Rabinowitsch fluid model, the effects of dilatant fluids (a non-Newtonian factor less than 0) and pseudo-plastic fluids (a non-Newtonian factor greater than 0) on the non-linear stability of hydrodynamic journal bearings is discussed. The modified Reynolds equation is solved by the small perturbation method, and the stiffness and damping coefficients and threshold speed of hydrodynamic bearings are obtained. Through the fourth-order Runge–Kutta method, the trajectory of the journal center is traced and the non-linear stability boundary of hydrodynamic bearings with different non-Newtonian lubricants could be confirmed. The results show that the dilatant fluids could increase the threshold speed and enlarge the non-linear stability region of the hydrodynamic bearing, while the influence of pseudo-plastic fluids is positive. And for the lubricants with a larger non-Newtonian factor, the effect is more obvious. It could be confirmed that the stability of hydrodynamic bearings lubricated with dilatant fluids is better than that of bearings with Newtonian and pseudo-plastic lubricants. The results illustrate that selecting a more appropriate lubricant can enhance the stability of hydrodynamic bearings.